The impact of productive services on the technological complexity of agricultural exports and the moderating role of environmental regulations - He, Guoping; Zeng, Zhihua (Frontiers in Environmental Science, 2024)
The integration of socialized services and green development are two major trends shaping modern agriculture. Similarly, the increasing technological complexity of exports has become a defining characteristic of contemporary agricultural trade. However, the relationship between agricultural services and the technological complexity of agricultural exports, as well as the potential influence of environmental regulations on this relationship, remains underexplored. This study utilizes provincial panel data from mainland China spanning 2007 to 2022 to investigate the impact of agricultural productive services on the technological complexity of agricultural exports. It also examines the mechanisms behind this impact and the moderating effects of different types of environmental regulations. The findings reveal that agricultural productive services significantly and robustly enhance the technological complexity of agricultural exports by fostering agricultural technological Advances and alleviating financial constraints. Furthermore, the study identifies varying moderating effects of environmental regulations. Command-and-control and voluntary public environmental regulations significantly amplify the positive impact of productive services on export complexity, whereas market-based environmental regulations show no significant effect. These findings suggest that promoting the development of agricultural services and optimizing environmental regulation policies are critical to enhancing the technological sophistication and sustainability of agricultural exports.